2015
DOI: 10.1055/s-0035-1552925
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Surgical Approaches on the Perioperative Level of Circulating Tumor Cells in Patients with Non-Small Cell Lung Cancer

Abstract: Background To observe and compare the effects of video-assisted thoracoscopic surgery (VATS) and conventional thoracotomy on the levels of circulating tumor cells (CTCs) in patients with non-small cell lung carcinoma (NSCLC). Methods Seventy-nine patients with a diagnosis of NSCLC were enrolled in the study. Forty-three were treated with VATS and 36 were treated with conventional thoracotomy. Blood samples were collected 3 days prior to surgery (d-3), during surgery (d0), and 3 days after surgery (d3). After e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The increased yield from the tumor outflow as well as the higher numbers found after resection of the tumor suggests a release of the cells directly from the tumor tissue which could also be amplified by the manipulation during resection. However there is some data suggesting a significance of manipulation for tumor cell dissemination, it remains unclear to what extent surgical techniques impact tumor cell shedding into the circulation and if they do, what the capabilities of the released cells concerning further metastasization are 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The increased yield from the tumor outflow as well as the higher numbers found after resection of the tumor suggests a release of the cells directly from the tumor tissue which could also be amplified by the manipulation during resection. However there is some data suggesting a significance of manipulation for tumor cell dissemination, it remains unclear to what extent surgical techniques impact tumor cell shedding into the circulation and if they do, what the capabilities of the released cells concerning further metastasization are 21 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the explanations was that laparoscopic approaches might enhance tumor cell detachment and mobilization. However, other studies showed that laparoscopy does not increase CTC release compared with open surgery [ 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two-thirds of the patients with lung cancer with a potentially curative tumor resection will present tumor recurrence and/or disseminated disease [ 62 ]. According to Huang et al, lung cancer cells may disseminate immediately after surgical resection [ 64 ]. Therefore, the 5-year survival rate has been dismal in the past two decades [ 65 , 66 ].…”
Section: Lung Cancermentioning
confidence: 99%